Hormesis Against Aging and Diseases: Using Properties of Biological Adaptation for Health and Survival Improvement - A. I. Yashin (SAGE Publishing, 2010)
The idea of using hormesis for postponing aging and improving human health has been recently discussed in scientific literature. This paper shows that redundancy in renewal capacity, some portion of which become activated and manifested in hormesis effects, may originate as a result of interaction between living organisms and their environment. It is shown that such redundancy may normally exist for organisms in the wild, and not only in domesticated and laboratory animals. Further development of the hormesis idea requires: (i) investigating regularities of response to multiple stimuli; (ii) studying slow-time responses (e.g., physiological adaptation) to repeated stimuli; (iii) studying connection between slow and fast (e.g., developing at the cellular and sub-cellular levels) stress responses; (iv) translating knowledge accumulated in studies of animal model systems to humans; (v) evaluating unrealized potential for improving health and longevity using hormetic mechanisms. The use of mathematical and computer modeling for translating experimental knowledge about hormesis effects to humans, as well as connection between studying hormetic mechanisms and analyses of the age trajectories of physiological and biological indices affecting U-shapes curves of morbidity-mortality risks using longitudinal data on aging, health, and longevity are discussed.